The role of job crafting in the relationship between empowering leadership and happiness at work: An empirical analysis - Mohammed Yasin Ghadi; Khaled Salameh Almanaga'h (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The purpose of this study is to examine a hypothesized model investigating the impact of empowering leadership on happiness at work through the mediating role of job crafting. A translated pre-determined survey on a sample of Jordanian academics was used. A total of 325 usable returns were collected for the analysis (i.e. a response rate of 84.6 percent). Structural equation model (SEM) using AMOS was implemented to obtain the best-fit model and to determine the role of job crafting as a potential mediator between empowering leadership and happiness at work. The results indicated no direct statistical effect for empowering leadership on happiness at work with an estimated value of 0.17 and a standard error of 0.073. The results also show that there was a significant statistical effect for empowering leadership on crafting and this effect was high with a value of 0.479 and a standard error of 0.040. Finally, the results revealed a direct effect for empowering leadership on happiness at work through the mediating role of job crafting. The study recommended that it is necessary for universities to offer new programs and workshops that improve the behaviors of empowering leadership in light of work conditions at various levels and to motivate job crafting to increase levels of happiness at work.
Keywords: M12; M14; 650; empowering leadership; job crafting; task crafting; relationship crafting; happiness at work